STRATEGI PENGEMBANGAN SCIENCE TECHNO PARK MELALUI EKOSISTEM INOVASI DALAM RANGKA PENINGKATAN DAYA SAING DAERAH PROVINSI SUMATERA SELATAN - Sari, Nila Mayang; Retnaningsih, Ekowati (Publikasi Penelitian Terapan dan Kebijakan, 2020)
The leading national issue discussing is the low adoption of domestic research and technology results by industry or other technology users. This study's purpose was to evaluate strategy for the development of the South Sumatra Science Techno Park (STP) within the framework to increase regional competitiveness through regional innovation systems. The study conducted through qualitative methods in the policy research approach. Factors that influence STP development, both supporting and inhibiting, discussed. The data collected through interviews, collection, and observation. The Strategic Development Strategy for South Sumatra's STP desperately requires massive resource mobilization, focus, and active participation of stakeholders, from the central to the local government, in the competition units of government or villages. Certain stages must be passed and carried out in the development of superior competition areas.